Enhancing economics learning outcomes through the make-a-match cooperative learning model - Sri Hardianti Sartika; Rohanna Iriana Harahap; Ati Sadiah (Educenter : Jurnal Ilmiah Pendidikan, 2024)
Learning outcomes reflect the extent to which students understand the material taught and how well they can apply that knowledge in practical situations. This research focuses on the low student learning outcomes in Economics lessons at the high school level. This research aims to determine the increase in student learning results by applying the Cooperative Learning type learning model Make a Match. The research method is a quasi-experimental quantitative approach. The population was 205 SMAN 7 Tasikmalaya class XI science students who study economics. The sampling technique used purposive sampling to obtain 68 students in two classes. The class is divided into two, namely experiments with learning models: Cooperative Learning Make a Match type and control class using models conventional with the lecture method. Technique data collection with 30 multiple-choice test questions. The research results showed statistically significant differences in the increase in student learning outcomes in the experimental class using the Make a Match type Cooperative Learning model and the control class using the conventional model after being given treatment. Thus, the application of the Cooperative Learning model with material designed to be more interactive as an alternative to conventional models can be used to improve student learning outcomes.